Old Yeller - Gipson, Fred, 1908- ([New York] : Buccaneer, 1956)
Fourteen-year-old Travis is left to take care of his mother and small brother in the Texas wilderness while his father is away, and is able to do so with the help of a big yellow dog.
Keywords: Dogs -- Fiction; Frontier and pioneer life -- Fiction; Dogs -- Fiction; Frontier and pioneer life -- Fiction; Frontier and pioneer life -- Fiction -- Texas; Texas -- Fiction; Texas -- Fiction